Targeted inhibition of STAT3 as a potential treatment strategy for atherosclerosis - Chen, Qi; Lv, Jianjun; Yang, Wenwen; Xu, Baoping; Wang, Zheng; Yu, Zihao; Wu, Jiawei; Yang, Yang; Han, Yuehu (Theranostics, 2019)
Atherosclerosis is the main pathological basis of ischemic cardiovascular and cerebrovascular diseases and has attracted more attention in recent years. Multiple studies have demonstrated that the signal transducer and activator of transcription 3 (STAT3) plays essential roles in the process of atherosclerosis. Moreover, aberrant STAT3 activation has been shown to contribute to the occurrence and development of atherosclerosis. Therefore, the study of STAT3 inhibitors has gradually become a focal research topic. In this review, we describe the crucial roles of STAT3 in endothelial cell dysfunction, macrophage polarization, inflammation, and immunity during atherosclerosis. STAT3 in mitochondria is mentioned as well. Then, we present a summary and classification of STAT3 inhibitors, which could offer potential treatment strategies for atherosclerosis. Furthermore, we enumerate some of the problems that have interfered with the development of mature therapies utilizing STAT3 inhibitors to treat atherosclerosis. Finally, we propose ideas that may help to solve these problems to some extent. Collectively, this review may be useful for developing future STAT3 inhibitor therapies for atherosclerosis.